THE EFFECT OF ORGANIZATIONAL COMMITMENT AND COMPENSATION ON TURNOVER INTENTION WITH JOB SATISFACTION AS AN INTERVENING VARIABLE FOR EMPLOYEES OF PT INTERCOM PADANG - Yunita Yunita (Dinasti Publisher, 2020)
This study aims to determine how much influence organizational commitment and organizational commitment and compensation as the independent variable (X) and job satisfaction as an intervening variable (Z). The analytical method used in this research is the path analysis model. Based on it can be concluded that organizational commitment has a negative and significant effect on employee turnover intention at PT Intercom Padang (0.000 <0.05). Based on the results of testing the second hypothesis, it was found that compensation had a negative effect on turnover intention (0.000 <0.05). Based on the results of testing the third hypothesis that organizational commitment has a negative and significant effect on employee job satisfaction at PT Intercom Padang. (0.000 <0.05). In the fourth hypothesis testing stage, it was found that compensation had a negative effect on job satisfaction. employees at PT Intercom Padang Branch. (0.001 <0.05). while the results of testing the fifth hypothesis found that job satisfaction has a negative effect on turnover intention). With the fulfillment of these requirements, it can be proven that organizational commitment and compensation have an effect on turnover intention after going through job satisfaction as an intervening variable for employees of PT Intercom Padang.